2021
DOI: 10.4041/kjod.2021.51.3.157
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different micro-osteoperforation depths on the rate of orthodontic tooth movement: A single-center, single-blind, randomized clinical trial

Abstract: Objective This study aimed to identify the clinical effectiveness of two different penetration depths of micro-osteoperforations (MOPs) on the rate of orthodontic tooth movement. Methods Twenty-four patients requiring the removal of the upper first premolar teeth were selected and randomly divided into two groups. The control group participants did not undergo MOPs. Participants in the experimental group underwent three MOPs each at 4-mm (MOP-4) and 7-mm (MOP-7) depths,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 30 publications
(49 reference statements)
1
1
0
1
Order By: Relevance
“…Due to lack of nutrition, the cortical repair capacity is compromised, and the cells of the bone marrow are recruited, elevating the degree of tooth movement [ 36 ]. This theory is supported by the results of a previous study that observed no acceleration of tooth movement for 7-mm-deep perforations in comparison to 4-mm-deep perforations, suggesting that increasing the surgical trauma by deepening MOPs is not more effective for the acceleration of tooth movement [ 39 ].…”
Section: Discussionsupporting
confidence: 60%
“…Due to lack of nutrition, the cortical repair capacity is compromised, and the cells of the bone marrow are recruited, elevating the degree of tooth movement [ 36 ]. This theory is supported by the results of a previous study that observed no acceleration of tooth movement for 7-mm-deep perforations in comparison to 4-mm-deep perforations, suggesting that increasing the surgical trauma by deepening MOPs is not more effective for the acceleration of tooth movement [ 39 ].…”
Section: Discussionsupporting
confidence: 60%
“…La información sobre los efectos de la piezocisión y las micro osteoperforaciones está basada en 31 ensayos aleatorizados que incluyeron 898 pacientes. 14 ensayos (48)(49)(50)(51)(52)54,56,61,62,69,70,(72)(73)(74) evaluaron la piezocisión (367 pacientes) y 17 ensayos (46,47,53,55,(57)(58)(59)(60)(63)(64)(65)(66)(67)(68)71,75,76 ) evaluaron las micro osteoperforaciones (531 pacientes).…”
Section: Resumen De Los Resultadosunclassified
“…Selective alveolar decortication caused a threefold increase in anabolic activity (bone deposition) and catabolic activity (bone degradation) in rats three weeks after corticotomy [ 11 ]. Additionally, osteotomy is a surgical procedure that increases the extent of the injury to both the cortical and trabecular bone and quickens tooth movement [ 12 , 13 , 14 ]. The Le Fort I osteotomy was shown to accelerate alveolar bone remodeling and orthodontic tooth movement in rats [ 15 ].…”
Section: Introductionmentioning
confidence: 99%